2022
DOI: 10.3390/ph15121486
|View full text |Cite
|
Sign up to set email alerts
|

Effects of o,p’-DDE, a Mitotane Metabolite, in an Adrenocortical Carcinoma Cell Line

Abstract: In South Brazil, the incidence of pediatric adrenocortical carcinoma (ACC) is higher than in other regions and countries worldwide. The ACC treatment includes therapy with mitotane, the only adrenolytic drug approved by the FDA. The mitotane metabolism occurs via two main reactions: the β-hydroxylation, which yields the final product o,p’-DDA, and the α-hydroxylation, which will give the final product o,p’-DDE. It is speculated that o,p’-DDE may be an active metabolite since it has a cytotoxic effect on adreno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…These transformations are mediated by the CYP450 family, an active enzyme system that is highly expressed in the adrenal gland. It has been demonstrated that DDE is an active metabolite of mitotane, although it is present at low plasma concentrations, while it is still debated whether DDA is active or not [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…These transformations are mediated by the CYP450 family, an active enzyme system that is highly expressed in the adrenal gland. It has been demonstrated that DDE is an active metabolite of mitotane, although it is present at low plasma concentrations, while it is still debated whether DDA is active or not [10,11].…”
Section: Introductionmentioning
confidence: 99%